Bibliometric analysis of global research trends on pyroptosis in lung disease - Mo, Wei; Li, Quanfu; Zhou, Huanping; Shi, Xuan; Yang, Hao; Xiao, Zhuoran; Wei, Juan; Lv, Xin (Frontiers in Immunology, 2022)
Background Pyroptosis is a lytic pro-inflammatory programmed cell death mode that depends on caspase, inflammasome, and Gasdermin D (GSDMD). A growing number of studies have shown that pyroptosis is closely related to the pathophysiological mechanism of lung. The purpose of this study is to analyze the literature from Science Citation Index Expanded (SCI-expanded) of Web of Science Core Collection (WoSCC) and visualize the current trends and hotspots in the research of pyroptosis in lung disease. Methods On February 20, 2022, we retrieved all articles on pyroptosis in lung disease from SCI-expanded of WoSCC. Original articles and reviews published in English from 2007 to 2021 were included in the analysis. VOSviewer 1.6.17 and CiteSpace 5.8.R2 were used to analyze the retrieved data and visualize the results. Result 1798 qualified original articles and reviews on pyroptosis in lung disease were included in the bibliometric analysis. So far, the research in this field is still in a period of growth, and the number of global publications has increased yearly. Among the 66 countries that have published relevant articles, China ranked first in the number of publications, and the USA ranked first in the number of cited articles. Holian,A. was the author with the largest number of articles, including 21 published. The University of California System in the USA was the organization with the largest number of articles, totaling 55. Frontiers in Immunology was the journal with the most publications in pyroptosis. After bibliometric analysis, the frequently used keywords are: “NOD-like receptor3 (NLRP3) inflammasome”, “inflammation”, “oxidative stress”, and “acute lung injury (ALI)”. Conclusion The research on pyroptosis in lung disease is in its growth stage. The information released in this article may help researchers better understand the hotspots and developmental trends in this field, the cooperation network information of authors, countries, and institutions, and the citation correlation between articles. With the in-depth study of the mechanism of pyroptosis, the focus has shifted to increasing research on the connections and influences of different diseases. So far, increasing attention has been paid to the research field of the relationship between ALI and pyroptosis related to COVID-19.